Reseña. Ecolinguistics: Language, Ecology and the Stories We Live By - Delgado Hernández, Cristián (Árboles y Rizomas, 2023)
The ever-accelerating destruction of life-supporting ecological systems is calling into question some of the fundamental stories we live by: stories of consumerism, progress, individualism, success, and human domination of nature. In Ecolinguistics: Language, Ecology and the Stories We Live By, Arran Stibbe shows how linguistic analysis can help unravel these stories, open them up for questioning, and contribute to the search for new stories. This book charts a new course for ecolinguistics as an engaged form of critical inquiry.